Characterization and Purification of Mouse Mucosal‐Associated Invariant T (MAIT) Cells. (23rd September 2019) - Chen, Zhenjun; Wang, Huimeng; D'Souza, Criselle; Koay, Hui‐Fern; Meehan, Bronwyn; Zhao, Zhe; Pediongco, Troi; Shi, Mai; Zhu, Tianyuan; Wang, Bingjie; Kjer‐Nielsen, Lars; Eckle, Sidonia B. G.; et al.
Abstract: This unit describes the utility of various mouse models of infection and immunization for studying mucosal‐associated invariant T (MAIT) cell immunity: MAIT cells can be isolated from the lungs (or from other tissues/organs) and then identified and characterized by flow cytometry using MR1 tetramers in combination with a range of antibodies. The response kinetics, cytokine profiles, and functional differentiation of lung MAIT cells are studied following infection with the bacterial pathogen Legionella longbeachae or Salmonella enterica Typhimurium or immunization with synthetic MAIT cell antigen plus Toll‐like receptor agonist. MAIT cells enriched or expanded during the process can be used for further studies. A step‐by‐step protocol is provided for MAIT cell sorting and adoptive transfer. Mice can then be challenged and MAIT cells tracked and further examined. © 2019 by John Wiley & Sons, Inc.